Sources of negative emotions and tactics of self-emotion regulation among college students during COVID-19 school closure in China - Fu, Hai; Pan, Mingfeng; Lai, Mingdong (Frontiers in Public Health, 2024)
This study investigated the level of anxiety and depression in Chinese college students since the COVID-19 pandemic and explored the sources of their negative emotions and students' self-emotion regulation strategies. Methods: A stratified cluster sampling questionnaire was used to survey college students during the pandemic via the Anxiety Depression, Self-made Negative Emotion Source, and Negative Emotion Regulation Strategy Scales. Results: The prevalence of anxiety and depression was 23.3% and 20.1%, respectively. These levels were higher in females than in males. Furthermore, senior students reported higher levels than freshmen. Anxiety and depression mainly came from the pressure to grow and narrowed scope of social activities. Proper relaxation via entertainment and communication with family and friends were popular ways of regulating their negative emotions. Conclusion: College students should confront their negative emotions and understand their source, use psychological methods to regulate their anxiety and depression or seek professional help, improve their psychological resilience, and adopt positive coping measures.